Making critical sense of immigrant experience : a case study of Hong Kong Chinese in Canada - Hilde, Rosalie K. S. (Critical management studies (Series)., 2017)
This book showcases a critical sensemaking (CSM) study of how professional immigrants from Hong Kong to Canada make sense of their workplace experiences, and what this can tell us about why a substantial number leave in their first year in Canada. An analysis of the interviews demonstrates that immigrants' identities are grounded by contextual sensemaking elements. Data show that informants have accepted unchallenged assumptions: (1) that the government is providing help for them to "get in" the workplace; and (2) that the ethnic service organizations are offering positive guidance to their workplace opportunities. At the organizational level, a master discourse emphasizing integration has mediated immigrants' struggles. Within these frustrations, many have internalized a hidden discourse of inadequate or deficient selves and adopted a sacrificial position to maintain a positive sense of identity. The study concludes that a critical sensemaking approach allows greater insights into immigration processes than realist surveys, which tend to impose a pre-packaged sense of the immigrant experience. Through critical sensemaking, readers are encouraged to rethink the current role of ethnic service organizations in the immigration system.